Ultrasound Characterization of Abdominal Wall Endometriosis - Mohammed Bader Hassan, Omar Muayad Sultan2 , Adnan Mohammed Brayyich3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background:Aim: Our aim in this study is to define the ultrasound finding in the patients have abdominal wall mass proven by postoperative histopathology as abdominal wall endometriosis. Patients & Methods: A cross sectional study was done from first of August 2016- first of September 2019 in Baghdad governorate. The study included 32 patients. Diagnosis done by superficial ultrasound examination. Results: 32 female have done at least 1 Cesarean section the commenst presenting symptom was pain in 90% of patients , all the lesions were hypoechoic in texture , with heterogeneity and small foci of echogenisity in 75% of our population , the consistency of the lesions was purely sold in 93.8% of lesions ,on color Doppler only 18.7% was avascular , the resistive index of the arterial flow was below 0.70 in 31 % of patients ,on elastography 78.5% of lesions was hard , the accuracy of assessment of muscle infiltration was 71% ,the ultrasound was the only imaging required preoperatively in 85% of our patients , the ultrasound was able to discriminate between endometrioma and collection or hernias in all patients and was the in the differential diagnosis list in about 90% of our population Conclusion: the ultrasound characteristics of abdominal wall endometriosis if combined with clinical features and symptoms of the patients is excellent preoperative imaging modality to reach the diagnosis and exclude other lesions and accurately assessing muscle invasion in most of cases for proper surgical planning